Recommendations for selection of a liquid stationary phase and geometric parameters of the column when determining triethylamine by gas chromatography - A. N. Ioutsi; M. A. Sumtsov; A. T. Sarnitskaya; A. N. Blinov (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article summarises the results of experimental studies that compared liquid stationary phases used in GC for determination of triethylamine residual solvent in medicinal products. It discusses the results of comparative evaluation of triethylamine peak area RSDs, retention times and tailing factors for different phases and solvents. The authors give recommendations concerning selection of chromatographic columns for triethylamine determination.